A multi-layer colorful ceramic and its preparation method
By optimizing the glue pattern material formula and the preparation of dry grain layers, the problems of unstable ceramic color materials and non-melting of dry grains in the prior art are solved, and the clear, uniform and wear-resistant effects of multi-layer colorful ceramics are achieved.
Patent Information
- Application Number
- CN202510041721.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the prior art, the components of the glue pattern material are incompatible, the ceramic color material is prone to agglomeration or decomposition and discoloration, and the glue pattern material does not melt with the dry particles, resulting in defects on the surface of the ceramic, resulting in poor multi-layered colorful effect.
Using an optimized glue pattern material formula, including ceramic colorants, adhesives, dispersants, solvents, stabilizers, surfactants and sodium phosphate, a digital glue pattern layer is formed by inkjet printing, and transparent frit dry particles and zircon sand dry particles are applied thereon. A multi-layer digital glaze layer is formed by repeated operations, and finally a protective glaze layer is added and fired.
The stable coloration of ceramic color materials is achieved, the clear positioning of the glue pattern layer, and the uniform distribution of the dry grain layer are achieved, forming a clear, uniform and multi-layered colorful effect, while improving the wear resistance of ceramics and preventing glaze defects.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building ceramic preparation, and in particular to a multi-layered colorful ceramic and a preparation method thereof. Background Art
[0002] The main ceramic surface decoration technologies include hand-painting, screen printing, digital thermal transfer and inkjet printing. Hand-painting is a handicraft technology that can bring unique beauty and value to ceramic products. However, hand-painting requires a long production time, which is a disadvantage for large-scale production. Compared with other ceramic surface decoration technologies, screen printing technology is low-cost, easy to operate, and can be processed on ceramic products of different shapes and sizes. It can easily change the design and printing position, and has the advantage of flexibility. However, the printing layer produced by screen printing on the ceramic surface will increase the weight of the ceramic, and has the disadvantages of easy falling off and limited resolution. Thermal transfer is a printing method that transfers the printed matter on the printing paper to the target object through high temperature and high pressure. Thermal transfer technology has high precision and good durability, but its use is not only complicated and costly, but also limited by materials and has a narrow range of applications. Ceramic inkjet printing technology is an emerging digital printing technology in recent years. Inkjet printing has the advantages of low cost, less material loss, high precision and versatility on substrates, which effectively improves the work efficiency and decorative effect of the ceramic surface decoration industry. In the prior art, inkjet printing is combined with glue positioning, and digital inkjet is combined with glue and dry particle fabric technology to produce ceramic products with a certain mold effect and dry particle texture. However, there are problems such as incompatibility of glue pattern material components, easy aggregation or decomposition and discoloration of ceramic colorants, and the non-melting of glue pattern materials and dry particles will also cause defects on the ceramic surface, resulting in poor color effects.
[0003] For example, the Chinese patent number CN116003168A discloses a glazed tile with an inkjet-printed three-dimensional pattern and a preparation method thereof. However, too much transparent isolation glaze has high fluidity at high temperatures, which can easily lead to ink seepage and then blur and distort the pattern, resulting in poor inkjet printing effect. Another example is the Chinese patent application number CN201911410866.9, which discloses a preparation process for colorful ceramic products imitating natural textures, including pretreatment, material selection, grading, proportioning preparation, iron removal, drying, pressing, metallographic testing, isostatic pressing and degreasing sintering; zirconium oxide ceramic powder is selected, and the preparation process can make ceramic products present a variety of colors, achieving color consistency inside and outside the colorful ceramic products, but the colorful effect still has room for improvement. Therefore, it is of positive significance to optimize and improve the raw materials and processes for the preparation of colorful ceramics. Summary of the invention
[0004] Based on this, in order to solve the problems in the prior art that the components of the glue pattern material are incompatible, the ceramic colorant is easy to agglomerate or decompose and discolor, and the glue pattern material and the dry particles are not melted, which will also cause defects on the ceramic surface, resulting in poor multi-level colorful effects, the present invention provides a multi-level colorful ceramic and a preparation method thereof, and the specific technical scheme is as follows:
[0005] A multi-layered colorful ceramic, comprising a ceramic body, a bottom glaze layer covering the surface of the ceramic body, at least two digital glaze layers covering the surface of the bottom glaze layer, and a protective glaze layer covering the digital glaze layer, wherein the digital glaze layer comprises a digital glue pattern layer and a dry particle layer arranged in sequence;
[0006] The digital glue pattern layer includes the following raw materials in parts by weight: 25 to 35 parts of ceramic pigment, 12 to 20 parts of adhesive, 1 to 3 parts of dispersant, 25 to 32 parts of solvent, 1 to 3 parts of stabilizer, 1 to 5 parts of fatty alcohol polyoxyethylene ether, 1 to 2 parts of antimony-doped tin dioxide, 1 to 3 parts of surfactant, and 1 to 1.5 parts of sodium phosphate;
[0007] The dry particle layer comprises the following raw materials in parts by weight: 100 parts of transparent frit dry particles and 20 to 35 parts of zircon sand dry particles.
[0008] Furthermore, the ceramic colorant includes at least one of a blue colorant, a red colorant, a yellow colorant, a black colorant, a green colorant, and a brown colorant.
[0009] Furthermore, the adhesive is at least one of polyvinyl alcohol and polyvinyl pyrrolidine.
[0010] Furthermore, the dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of (1-5):1.
[0011] Furthermore, the solvent is at least one of dioctyl adipate, triethylene glycol diisooctyl ester, triethylene glycol butyl ether and methyl oleate.
[0012] Furthermore, the stabilizer is at least one of methyltin mercaptan and octyltin mercaptan.
[0013] Furthermore, the surfactant is at least one of alkanolamide, fatty acid alkanolamide, alkylphenol polyoxyethylene ether sodium oleate, sodium stearate, sodium petroleum sulfonate, sodium dodecyl sulfate and hexadecyltrimethylammonium bromide.
[0014] Furthermore, the transparent frit dry particles include the following components in percentage by mass:
[0015] SiO2: 40~55%, Al2O3: 15~19%, BaO: 10%~15%, ZnO: 7.5%~12.6%, Fe2O3: 0.1%~1%, TiO2: 0.5~0.8%, Na2O: 1~3%, CaO: 1%~4%, MgO: 1.2%~5.3%, K2O: 1.5~3.7% and loss on ignition: 1~5%.
[0016] In addition, the present invention also provides a method for preparing multi-layer colorful ceramics, the preparation method comprising the following steps:
[0017] Applying a base glaze on the surface of the ceramic body to form a base glaze layer;
[0018] Prepare a glue pattern material, inkjet print the glue pattern material on the surface of the base glaze layer to form a digital glue pattern layer, then apply dry particles on the digital glue pattern layer to form a dry particle layer, and recover the dry particles not adhering to the digital glue pattern layer through an absorption system, repeat the above operation according to the designed number of layers, and after drying, form at least two layers of digital glaze layers;
[0019] A protective glaze is applied on the surface of the digital glaze layer to form a protective glaze layer, and after firing treatment, a multi-layered colorful ceramic is obtained.
[0020] Furthermore, the preparation method of the glue pattern material is:
[0021] After the ceramic pigment is pulverized by air flow, fine ceramic pigment powder with a particle size of 15 μm to 40 μm is obtained;
[0022] The ceramic colorant fine powder, adhesive, solvent, fatty alcohol polyoxyethylene ether and antimony-doped tin dioxide are added to a ball mill, heated to 60°C~80°C for primary ball milling for 6h~10h to obtain a mixed slurry with an average particle size of 0.5μm~5μm; then, a dispersant, a stabilizer, a surfactant and sodium phosphate are added to the mixed slurry, heated to 65°C~80°C for secondary ball milling for 3h~5h to obtain a glue pattern material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention optimizes the glue pattern material and adds ceramic colorants to the digital glue pattern layer. No dry particle colorants need to be added, and the ceramics can be given a specific color appearance. The ceramic colorants are not easy to fade at high temperature, that is, the color development stability is good. After the inkjet printing process, the material diffusion phenomenon can also be reduced, and the formed pattern has a clear outline and uniform coloring. The digital glue pattern layer; wherein, the addition of compounded pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate as dispersants can provide attachment ligands for the ceramic colorants, significantly improving the dispersion stability of the ceramic colorants, and further combining antimony-doped tin dioxide can effectively reduce electrostatic adsorption and further promote the stability of the system, and adding fatty alcohol polyoxyethylene ether and sodium phosphate can increase the adhesion and improve the adhesion stability with the dry particles. Under the action of the surfactant, the surface tension is suitable, and the uniform adhesion of the dry particles is further promoted, so as to achieve the purpose of excellent glue positioning, and form a dry particle layer with uniform dispersion and a pattern consistent with the digital glue pattern layer.
[0025] 2. The present invention preferably uses transparent frit dry particles and zircon sand dry particles as raw materials for preparing the dry particle layer, which have better compatibility with the glue pattern material with high temperature viscosity. The zircon sand can be dispersed in the transparent frit dry particles by repeatedly inkjet printing the glue pattern material-applying the dry particles, and further grows with the zircon sand as the crystallization carrier. The crystal morphology is sharp, which can not only increase the wear resistance of the ceramic, but also form a ceramic appearance with a multi-layer colorful effect when combined with the ceramic colorant.
[0026] 3. The digital glaze layer of the present invention has a high degree of compatibility and adaptability. After firing, it can effectively prevent the digital glaze layer and the protective glaze from having defects such as micro cracks on the glaze surface due to incompatibility, thereby affecting the apparent quality of the ceramics. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0028] A multi-layered colorful ceramic in one embodiment of the present invention comprises a ceramic body, a bottom glaze layer covering the surface of the ceramic body, at least two digital glaze layers covering the surface of the bottom glaze layer, and a protective glaze layer covering the digital glaze layer, wherein the digital glaze layer comprises a digital glue pattern layer and a dry particle layer arranged in sequence;
[0029] The digital glue pattern layer includes the following raw materials in parts by weight: 25 to 35 parts of ceramic pigment, 12 to 20 parts of adhesive, 1 to 3 parts of dispersant, 25 to 32 parts of solvent, 1 to 3 parts of stabilizer, 1 to 5 parts of fatty alcohol polyoxyethylene ether, 1 to 2 parts of antimony-doped tin dioxide, 1 to 3 parts of surfactant, and 1 to 1.5 parts of sodium phosphate;
[0030] The dry particle layer comprises the following raw materials in parts by weight: 100 parts of transparent frit dry particles and 20 to 35 parts of zircon sand dry particles.
[0031] In one embodiment, the ceramic colorant includes at least one of a blue colorant, a red colorant, a yellow colorant, a black colorant, a green colorant, and a brown colorant.
[0032] In one embodiment, the adhesive is at least one of polyvinyl alcohol and polyvinyl pyrrolidine.
[0033] In one embodiment, the dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of (1-5):1.
[0034] In one embodiment, the preparation method of the pyrrolidone-modified sulfonated lignin is as follows:
[0035] N-vinyl pyrrolidone and allyl glycidyl ether in a molar ratio of 1:1 are added to a reaction container, and deionized water is added as a solvent, and ammonium persulfate accounting for 1% to 2% of the total mass of N-vinyl pyrrolidone and allyl glycidyl ether is added dropwise, and the dropping time is controlled to be 20min to 30min, and heated to 80°C, and stirred for 5h to 6h under a nitrogen atmosphere to obtain a precursor;
[0036] The sulfonated lignin is added to the precursor, mixed evenly, heated to 95° C. to 100° C., and stirred for reaction for 3 h to 4 h to prepare pyrrolidone-modified sulfonated lignin.
[0037] In one embodiment, the solvent is at least one of dioctyl adipate, triethylene glycol diisooctyl ester, triethylene glycol butyl ether and methyl oleate.
[0038] In one embodiment, the stabilizer is at least one of methyltin mercaptan and octyltin mercaptan.
[0039] In one embodiment, the surfactant is at least one of alkanolamide, fatty acid alkanolamide, alkylphenol polyoxyethylene ether sodium oleate, sodium stearate, sodium petroleum sulfonate, sodium dodecyl sulfate and hexadecyltrimethylammonium bromide.
[0040] In one embodiment, the transparent frit dry particles include the following components in percentage by weight:
[0041] SiO2: 40%~55%, Al2O3: 15%~19%, BaO: 10%~15%, ZnO: 7.5%~12.6%, Fe2O3: 0.1%~1%, TiO2: 0.5%~0.8%, Na2O: 1%~3%, CaO: 1%~4%, MgO: 1.2%~5.3%, K2O: 1.5~3.7% and loss on ignition: 1~5%.
[0042] In one embodiment, the purity of the zircon sand dry particles is ≥95wt%.
[0043] In one embodiment, the grading of the zircon sand dry particles is: above 80 mesh: none, 80 mesh to 100 mesh: 5% to 20%, 100 mesh to 120 mesh: 15% to 25%, 120 mesh to 150 mesh: 20% to 30%, 150 mesh to 200 mesh: 15% to 20%, below 200 mesh: 20% to 35%.
[0044] In one embodiment, the grading of the transparent frit dry particles is: above 60 mesh: none, 60 mesh to 80 mesh: 5% to 15%, 80 mesh to 100 mesh: 10% to 20%, 100 mesh to 120 mesh: 15% to 25%, 120 mesh to 150 mesh: 25% to 30%, 150 mesh to 200 mesh: 15% to 25%, and below 200 mesh: 10% to 25%.
[0045] In one embodiment, the digital glaze layer consists of two layers.
[0046] In addition, the present invention also provides a method for preparing multi-layer colorful ceramics, the preparation method comprising the following steps:
[0047] Applying a base glaze on the surface of the ceramic body to form a base glaze layer;
[0048] Prepare a glue pattern material, inkjet print the glue pattern material on the surface of the base glaze layer to form a digital glue pattern layer, then apply dry particles on the digital glue pattern layer to form a dry particle layer, and recover the dry particles not adhering to the digital glue pattern layer through an absorption system, repeat the above operation according to the designed number of layers, and after drying, form at least two layers of digital glaze layers;
[0049] A protective glaze is applied on the surface of the digital glaze layer to form a protective glaze layer, and after firing treatment, a multi-layered colorful ceramic is obtained.
[0050] In one embodiment, the preparation method of the glue pattern material is:
[0051] After the ceramic pigment is pulverized by air flow, fine ceramic pigment powder with a particle size of 15 μm to 40 μm is obtained;
[0052] The ceramic colorant fine powder, adhesive, solvent, fatty alcohol polyoxyethylene ether and antimony-doped tin dioxide are added to a ball mill, heated to 60°C~80°C for primary ball milling for 6h~10h to obtain a mixed slurry with an average particle size of 0.5μm~5μm; then, a dispersant, a stabilizer, a surfactant and sodium phosphate are added to the mixed slurry, heated to 65°C~80°C for secondary ball milling for 3h~5h to obtain a glue pattern material.
[0053] In one embodiment, the specific gravity of the base glaze is 1.3 g / cm 3 ~1.7g / cm 3 .
[0054] In one embodiment, the amount of the base glaze applied is 200g / m 2 ~450g / m 2 .
[0055] In one embodiment, the base glaze includes the following components in mass percentage: SiO2: 56%~72%, Al2O3: 5.5%~12.7%, Na2O: 1.3%~5.5%, CaO: 0.1%~0.8%, MgO: 2.1%~2.5%, K2O: 1.7%~5.3%, ZnO: 1.1%~3.5%, ZrO2: 5%~10% and loss on ignition: 1~3%.
[0056] In one embodiment, the solid content of the glue pattern material is ≥50%.
[0057] In one embodiment, the inkjet printing amount of the glue pattern material is 80g / m 2 ~200g / m 2 .
[0058] In one embodiment, the amount of dry particles applied each time is 400 g / m 2 ~550 g / m 2 .
[0059] In one embodiment, the specific gravity of the protective glaze is 1.2 g / cm 3 ~1.5g / cm 3 .
[0060] In one embodiment, the amount of the protective glaze applied is 120 g / m 2 ~250g / m 2 .
[0061] In one embodiment, the protective glaze includes the following components in mass percentage: SiO2: 40%~55%, Al2O3: 20%~25.5%, Na2O: 3.2%~7.4%, CaO: 1%~3%, MgO: 1%~3%, K2O: 1.7%~5.3%, ZnO: 1.5%~5.6%, BaO: 2.5%~5% and loss on ignition: 1~5%.
[0062] In one embodiment, the sintering temperature is 1220° C. to 1260° C., and the sintering cycle is 45 min to 55 min.
[0063] The embodiments of the present invention will be described in detail below with reference to specific examples. Embodiment 1:
[0064] A multi-layered colorful ceramic, comprising a ceramic body, a bottom glaze layer covering the surface of the ceramic body, at least two digital glaze layers covering the surface of the bottom glaze layer, and a protective glaze layer covering the digital glaze layer, wherein the digital glaze layer comprises a digital glue pattern layer and a dry particle layer arranged in sequence;
[0065] The base glaze used in the base glaze layer includes the following components in mass percentage: SiO2: 69.8%, Al2O3: 8.35%, Na2O: 4.45%, CaO: 0.5%, MgO: 2.5%, K2O: 3.85%, ZnO: 2.17%, ZrO2: 7.23% and loss on ignition: 1.15%;
[0066] The digital glue pattern layer includes the following raw materials in parts by weight: 25 parts of ceramic pigment, 12 parts of polyvinyl alcohol, 3 parts of dispersant, 30 parts of dioctyl adipate, 1 part of methyl tin mercaptan, 3 parts of fatty alcohol polyoxyethylene ether, 2 parts of antimony-doped tin dioxide, 3 parts of alkylphenol polyoxyethylene ether sodium oleate, and 1 part of sodium phosphate, wherein the dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of 2:1;
[0067] The dry particle layer comprises the following raw materials in parts by weight: 100 parts of transparent frit dry particles and 30 parts of zircon sand dry particles with a purity of 97wt%;
[0068] The transparent frit dry particles include the following components in percentage by mass: SiO2: 41.5%, Al2O3: 17.08%, BaO: 12.37%, ZnO: 11.6%, Fe2O3: 1%, TiO2: 0.8%, Na2O: 3%, CaO: 3.25%, MgO: 5.12%, K2O: 3.2% and loss on ignition: 1.08%;
[0069] The grading of the transparent frit dry particles is: above 60 mesh: none, 60 mesh to 80 mesh: 5%, 80 mesh to 100 mesh: 10%, 100 mesh to 120 mesh: 15%, 120 mesh to 150 mesh: 25%, 150 mesh to 200 mesh: 20%, below 200 mesh: 25%;
[0070] The grading of the zircon sand dry particles is: above 80 mesh: none, 80 mesh to 100 mesh: 10%, 100 mesh to 120 mesh: 20%, 120 mesh to 150 mesh: 20%, 150 mesh to 200 mesh: 15%, below 200 mesh: 35%;
[0071] The protective glaze used in the protective layer includes the following components in mass percentage: SiO2: 52%, Al2O3: 22.5%, Na2O: 5.1%, CaO: 2.05%, MgO: 1.85%, K2O: 5.3%, ZnO: 5.6%, BaO: 4.26% and loss on ignition: 1.34%.
[0072] A method for preparing multi-layer colorful ceramics comprises the following steps:
[0073] 450g / m 2 Applying the bottom glaze on the surface of the ceramic body in an amount of , forming a bottom glaze layer;
[0074] The ceramic pigment is pulverized by air flow to obtain a ceramic pigment fine powder with a particle size of 20 μm; then the ceramic pigment fine powder, polyvinyl alcohol, dioctyl adipate, fatty alcohol polyoxyethylene ether and antimony-doped tin dioxide are added to a ball mill, heated to 65° C. for primary ball milling for 8 hours to obtain a mixed slurry with an average particle size of 1 μm; then a dispersant, methyl tin mercaptan, alkylphenol polyoxyethylene ether sodium oleate and sodium phosphate are added to the mixed slurry, heated to 80° C. for secondary ball milling for 5 hours to obtain a glue pattern material;
[0075] 180g / m 2 The glue pattern material is inkjet printed on the surface of the base glaze layer to form a digital glue pattern layer, and then the glue pattern material is printed at 400 g / m 2 The dry particles are applied on the digital glue pattern layer to form a dry particle layer, and the dry particles not attached to the digital glue pattern layer are recovered by the absorption system. According to the designed number of layers, the dry particles are applied again at 180g / m 2 The glue pattern material is inkjet printed to form a digital glue pattern layer, and then the glue pattern material is printed at 400 g / m 2 The dry particles are applied in an amount of , forming a dry particle layer, and the dry particles not adhering to the digital glue pattern layer are recovered by an absorption system, and after drying, two layers of digital glaze are formed;
[0076] 250g / m 2 A protective glaze is applied on the surface of the digital glaze layer to form a protective glaze layer. The firing temperature is 1220° C. and the firing cycle is 50 minutes to obtain multi-layered colorful ceramics. Embodiment 2:
[0077] The difference between Example 2 and Example 1 is that the raw material ratio of the digital glue pattern layer in Example 2 is different, and the rest is the same as Example 1, which is as follows in Example 2:
[0078] The digital glue pattern layer includes the following raw materials in parts by weight: 25 parts of ceramic colorant, 12 parts of polyvinyl alcohol, 2 parts of dispersant, 30 parts of dioctyl adipate, 1 part of methyl tin mercaptan, 3 parts of fatty alcohol polyoxyethylene ether, 2 parts of antimony-doped tin dioxide, 2 parts of alkylphenol polyoxyethylene ether sodium oleate, and 1 part of sodium phosphate, wherein the dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of 1:1. Embodiment 3:
[0079] The difference between Example 3 and Example 1 is that the raw material ratio of the digital glue pattern layer in Example 3 is different, and the rest is the same as Example 1. The raw materials for preparing the digital glue pattern layer in Example 3 are as follows:
[0080] The digital glue pattern layer includes the following raw materials in parts by weight: 25 parts of ceramic colorant, 15 parts of polyvinyl alcohol, 3 parts of dispersant, 32 parts of dioctyl adipate, 2 parts of octyltin mercaptide, 2 parts of fatty alcohol polyoxyethylene ether, 1 part of antimony-doped tin dioxide, 3 parts of fatty acid alkanolamide, and 1 part of sodium phosphate, wherein the dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of 2:1. Embodiment 4:
[0081] The difference between Example 4 and Example 1 is that the dry particle layer in Example 4 includes the following preparation raw materials in parts by weight: 100 parts of transparent frit dry particles and 35 parts of zircon sand dry particles, and the rest is the same as Example 1.
[0082] It should be noted that the ceramic pigments in the above-mentioned Examples 1 to 4 are all prepared by mixing conventional black pigments and brown pigments. The ceramic samples 1 to 4 prepared in the above-mentioned Examples 1 to 4 all show excellent flatness on the surface, no defects, clear patterns, excellent glue positioning effect, excellent wear resistance, and crystal glitter. By repeatedly inkjet printing the glue pattern material-applying dry particles, combined with the interaction of ceramic pigments, a multi-level colorful effect is presented.
[0083] Comparative Example 1:
[0084] The difference between Comparative Example 1 and Example 1 is that the raw material for preparing the digital glue pattern layer in Comparative Example 1 adopts a single pyrrolidone-modified sulfonated lignin as a dispersant, and the rest is the same as Example 1.
[0085] Comparative Example 2:
[0086] The difference between Comparative Example 2 and Example 1 is that the raw material for preparing the digital glue pattern layer in Comparative Example 2 uses a single 2-(dimethylamino)ethyl methacrylate as a dispersant, and the rest is the same as Example 1.
[0087] Comparative Example 3:
[0088] The difference between Comparative Example 3 and Example 1 is that no dispersant is added to the raw materials for preparing the digital glue pattern layer in Comparative Example 3, and the rest is the same as Example 1.
[0089] Comparative Example 4:
[0090] The difference between Comparative Example 4 and Example 1 is that conventional lignin is used in Comparative Example 4 to replace the pyrrolidone-modified sulfonated lignin, and the rest is the same as Example 1.
[0091] Comparative Example 5:
[0092] The difference between Comparative Example 5 and Example 1 is that no antimony-doped tin dioxide is added in Comparative Example 5, and the rest is the same as Example 1.
[0093] Comparative Example 6:
[0094] The difference between Comparative Example 6 and Example 1 is that no sodium phosphate is added in Comparative Example 6, and the rest is the same as Example 1.
[0095] Comparative Example 7:
[0096] The difference between Comparative Example 7 and Example 1 is that in Comparative Example 7, no transparent frit dry particles are added, that is, zircon sand dry particles are directly added, and the rest is the same as Example 1.
[0097] Comparative Example 8:
[0098] The difference between Comparative Example 8 and Example 1 is that the gradation of dry particles in Comparative Example 8 is different from that in Example 1, and the others are the same as Example 1. The mesh number of the transparent frit dry particles in Comparative Example 8 is 250 mesh, and the mesh number of the zircon sand dry particles is 250 mesh.
[0099] Comparative Example 9:
[0100] The difference between Comparative Example 9 and Example 1 is that the gradation of dry particles in Comparative Example 9 is different from that in Example 1, and the others are the same as Example 1. The mesh number of the transparent frit dry particles in Comparative Example 9 is 50 mesh, and the mesh number of the zircon sand dry particles is 30 mesh.
[0101] The ceramic samples of Examples 1 to 4 and the ceramic comparison samples of Comparative Examples 1 to 9 were subjected to glaze quality observation and glaze wear resistance test. The results are shown in Table 1 below.
[0102] Table 1: Performance test results
[0103] Project Category Glaze effect Glaze quality Wear resistance Example 1 The pattern of the digital glue pattern layer has clear outlines, and the glitter particles are evenly distributed in distinct layers, with excellent multi-layered colorful effects. The glaze surface is smooth, the glue positioning dry particles are excellent, and there are no obvious glaze defects. Level 4 Example 2 The pattern of the digital glue pattern layer has clear outlines, and the glitter particles are evenly distributed in distinct layers, with excellent multi-layered colorful effects. The glaze surface is smooth, the glue positioning dry particles are excellent, and there are no obvious glaze defects. Level 4 Example 3 The pattern of the digital glue pattern layer has clear outlines, and the glitter particles are evenly distributed in distinct layers, with excellent multi-layered colorful effects. The glaze surface is smooth, the glue positioning dry particles are excellent, and there are no obvious glaze defects. Level 4 Example 4 The pattern of the digital glue pattern layer has clear outlines, and the glitter particles are evenly distributed in distinct layers, creating a multi-layered colorful effect. The glaze surface is smooth, the glue positioning dry particles are excellent, and there are no obvious glaze defects. Level 4 Comparative Example 1 The pattern color material of the digital glue pattern layer is uneven, there are few glitter particles, and the colorful effect is average. The glaze is smooth, the glue positioning of the dry particles is average, and there are no obvious glaze defects. Level 4 Comparative Example 2 The pattern color material of the digital glue pattern layer is uneven, there are few glitter particles, and the colorful effect is average. The glaze is smooth, the glue positioning of the dry particles is average, and there are no obvious glaze defects. Level 4 Comparative Example 3 The pattern color material of the digital glue pattern layer is uneven and diffuse, there are few glitter particles, and the colorful effect is poor. The glaze surface is smooth, the glue positioning effect of dry particles is poor, and there are no obvious glaze defects. Level 3 Comparative Example 4 The pattern color material of the digital glue pattern layer is uneven, there are few glitter particles, and the colorful effect is average. The glaze is smooth, the glue positioning of the dry particles is average, and there are no obvious glaze defects. Level 4 Comparative Example 5 The pattern pigments in the digital glue pattern layer are clustered, there are few glitter particles, and the colorful effect is average. The glaze is smooth, the glue positioning of the dry particles is average, and there are no obvious glaze defects. Level 3 Comparative Example 6 The pattern outline of the digital glue pattern layer is clear, but there are few glitter particles and the colorful effect is average. The glaze is smooth, the glue positioning of the dry particles is average, and there are no obvious glaze defects. Level 4 Comparative Example 7 The pattern outline of the digital glue pattern layer is clear, the glitter particles are small, and the colorful effect is average. The agglomeration of glitter particles causes pinholes in the sintering process and defects in the glaze surface. Level 3 Comparative Example 8 The pattern outline of the digital glue pattern layer is clear, the glitter particles are few and small, and the colorful effect is poor. The effect of glue in positioning dry particles is poor, and the dry particles agglomerate to produce obvious glaze defects. Level 3 Comparative Example 9 The pattern outline of the digital glue pattern layer is clear, the glitter particles are few and abrupt, and the colorful effect is poor. The effect of glue positioning the dry particles is poor, the glaze surface is obviously uneven, and micro cracks appear. /
[0104] It can be analyzed from Table 1 that the present invention optimizes the raw materials for preparing the glue pattern layer and the raw materials for preparing the dry particle layer, so that the digital glue pattern layer has a clear outline, stable color, excellent glue positioning effect, and the dry particles can be evenly distributed on the glue pattern layer. The glue pattern layer has excellent adhesion and can adhere to more dry particles. The excellent compatibility enables the dry particles to combine with the ceramic colorants in the pattern layer to present a colorful flashing effect, and will not affect the surface quality of the glaze, and can also increase the wear resistance of the glaze. Specifically, the difference between Comparative Examples 1 to 4 and Example 1 is that different dispersants are used or no dispersant is added, but it can be seen that the preferred dispersant of the present application can not only increase the dispersibility of the ceramic colorant and promote the acquisition of a digital glue pattern layer with a clear outline, but also the glue pattern layer material with excellent stability can adhere to more dry particles, improve the glue positioning effect, and thus improve the colorful effect and wear resistance. The difference between Comparative Example 5 and Example 1 is that no antimony-doped tin dioxide is added in Comparative Example 5, and the electrostatic adsorption effect is increased, so that the dispersion of ceramic pigment is worse than that in Example 1, the glue positioning effect is poor, the dry particles have less adhesion, the colorful effect is average, and the wear resistance is also worse than that in Example 1. No sodium phosphate is added in Comparative Example 6, and sodium phosphate can promote the interface compatibility between the dry particles and the glue pattern layer material. The glue positioning effect of the dry particles is average, and the flash effect of the zircon sand dry particles cannot be better exerted. In Comparative Example 7, no transparent frit dry particles are added, and the zircon sand dry particles fail to crystallize and grow under the action of the transparent dry particles. Instead, the original edges and corners are melted and the edges and corners become rounded, showing a poor colorful effect, and the zircon sand dry particles also have the problem of agglomeration, resulting in poor glaze quality. The dry particles used in Comparative Example 8 have different grading, larger mesh size, smaller particles, obvious agglomeration, reduced dry particle adhesion, poor glue positioning effect of the dry particles, resulting in poor colorful effect and glaze defects, and the wear resistance is also worse than that of Example 1. In Comparative Example 9, different dry particle grading was used, with smaller mesh size and larger particles, resulting in poor glue positioning effect of dry particles. The dry particles failed to match the digital glue pattern layer, and the glaze surface was obviously uneven. After firing, the dry particles shrank, resulting in microcracks, and the preset ceramics could not be obtained.
[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. All processes similar to the present invention and equivalent changes made thereto should fall within the protection scope of the present invention.
Claims
1. A multi-layer colorful ceramic, comprising a ceramic body, a bottom glaze layer covering the surface of the ceramic body, at least two digital glaze layers covering the surface of the bottom glaze layer, and a protective glaze layer covering the digital glaze layer, characterized in that: The digital glaze layer includes a digital glue pattern layer and a dry particle layer arranged in sequence; The digital glue pattern layer includes the following raw materials in parts by weight: 25 to 35 parts of ceramic pigment, 12 to 20 parts of adhesive, 1 to 3 parts of dispersant, 25 to 32 parts of solvent, 1 to 3 parts of stabilizer, 1 to 5 parts of fatty alcohol polyoxyethylene ether, 1 to 2 parts of antimony-doped tin dioxide, 1 to 3 parts of surfactant, and 1 to 1.5 parts of sodium phosphate; The dispersant is obtained by mixing pyrrolidone-modified sulfonated lignin and 2-(dimethylamino)ethyl methacrylate in a mass ratio of (1-5):1; The surfactant is at least one of alkanolamide, sodium stearate, sodium petroleum sulfonate, sodium lauryl sulfate and hexadecyltrimethylammonium bromide; The dry particle layer comprises the following raw materials in parts by weight: 100 parts of transparent frit dry particles and 20 to 35 parts of zircon sand dry particles; The transparent frit dry particles include the following components in percentage by mass: SiO2: 40-55%, Al2O3: 15-19%, BaO: 10%-15%, ZnO: 7.5%-12.6%, Fe2O3: 0.1%-1%, TiO2: 0.5-0.8%, Na2O: 1-3%, CaO: 1%-4%, MgO: 1.2%-5.3%, K2O: 1.5-3.7% and loss on ignition: 1-5%; The grading of the transparent frit dry particles is: above 60 mesh: none, 60 mesh to 80 mesh: 5%, 80 mesh to 100 mesh: 10%, 100 mesh to 120 mesh: 15%, 120 mesh to 150 mesh: 25%, 150 mesh to 200 mesh: 20%, below 200 mesh: 25%; The grading of the zircon sand dry particles is: above 80 mesh: none, 80 mesh to 100 mesh: 10%, 100 mesh to 120 mesh: 20%, 120 mesh to 150 mesh: 20%, 150 mesh to 200 mesh: 15%, below 200 mesh: 35%.
2. The multi-layer colorful ceramic according to claim 1, characterized in that: The ceramic pigment includes at least one of a blue pigment, a red pigment, a yellow pigment, a black pigment, a green pigment, and a brown pigment.
3. The multi-layer colorful ceramic according to claim 1, characterized in that: The adhesive is at least one of polyvinyl alcohol and polyvinyl pyrrolidine.
4. The multi-layer colorful ceramic according to claim 1, characterized in that: The solvent is at least one of dioctyl adipate, triethylene glycol diisooctyl ester, triethylene glycol butyl ether and methyl oleate.
5. The multi-layer colorful ceramic according to claim 1, characterized in that: The stabilizer is at least one of methyltin mercaptan and octyltin mercaptan.
6. A method for preparing multi-layer colorful ceramics, characterized in that: The preparation method is used to prepare the multi-layered colorful ceramics according to any one of claims 1 to 5, and the preparation method comprises the following steps: Applying a base glaze on the surface of the ceramic body to form a base glaze layer; Prepare a glue pattern material, inkjet print the glue pattern material on the surface of the base glaze layer to form a digital glue pattern layer, then apply dry particles on the digital glue pattern layer to form a dry particle layer, and recover the dry particles not adhering to the digital glue pattern layer through an absorption system, repeat the above operation according to the designed number of layers, and after drying, form at least two layers of digital glaze layers; A protective glaze is applied on the surface of the digital glaze layer to form a protective glaze layer, and after firing treatment, a multi-layered colorful ceramic is obtained.
7. The preparation method according to claim 6, characterized in that: The preparation method of the glue pattern material is: After the ceramic pigment is pulverized by air flow, fine ceramic pigment powder with a particle size of 15 μm to 40 μm is obtained; The ceramic colorant fine powder, adhesive, solvent, fatty alcohol polyoxyethylene ether and antimony-doped tin dioxide are added to a ball mill, heated to 60°C~80°C for primary ball milling for 6h~10h to obtain a mixed slurry with an average particle size of 0.5μm~5μm; then, a dispersant, a stabilizer, a surfactant and sodium phosphate are added to the mixed slurry, heated to 65°C~80°C for secondary ball milling for 3h~5h to obtain a glue pattern material.
Citation Information
Patent Citations
Preparation process of natural-texture-imitated multicolor ceramic product and multicolor ceramic product
CN111087241A
Glazed tile containing three-dimensional patterns printed by ink-jet printing and preparation method of glazed tile
CN116003168A
Luxurious stone glaze ceramic tile and production method thereof
CN110615694A
Ink-jet printing decorative ink for domestic ceramics and preparation method for ink-jet printing decorative ink
CN111363410A
Pyrrolidone grafted lignin carboxylate as well as preparation method and application thereof
CN116217838A